Identification of NURR1 (Exon 4) and FOXA1 (Exon 3) Haplotypes Associated with mRNA Expression Levels in Peripheral Blood Lymphocytes of Parkinson’s Patients in Small Indian Population - Jayakrishna Tippabathani; Jayshree Nellore; Vaishnavie Radhakrishnan; Somashree Banik; Sonia Kapoor (Parkinson's Disease, 2017)
Here, we study the expression of NURR1 and FOXA1 mRNA in peripheral blood lymphocytes and its haplotypes in coding region in a small Chennai population of India. Thirty cases of Parkinson’s patients (PD) with anti-PD medications (20 males aged 65.85±1.19 and 10 females aged 65.7±1.202) and 30 age matched healthy people (20 males aged 68.45±1.282 and 10 females aged 65.8±1.133) were included. The expression of NURR1 and FOXA1 in PBL was detected by Q-PCR and haplotypes were identified by PCR-SSCP. In the 30 PD cases examined, NURR1 and FOXA1 expression was significantly reduced in both male and female PD patients. However, NURR1 (57.631% reduced in males; 28.93% in females) and FOXA1 (64.42% in males; 55.76% in females) mRNA expression did differ greatly between male and female PD patients. Polymorphisms were identified at exon 4 of the NURR1 and at exon 3 of the FOXA1, respectively, in both male and female patients. A near significant difference in SSCP patterns between genders of control and PD population was analyzed suggesting that further investigations of more patients, more molecular markers, and coding regions should be performed. Such studies could potentially reveal peripheral molecular marker of early PD and different significance to the respective genders.